Teaching the economics of standards at the tertiary level: Evidence from China - Yang, Lijuan (Universitas Negeri Semarang, 2025)
The economics of standards (EOS) plays a critical role in improving product quality, stabilizing markets, and enhancing efficiency, yet its integration into tertiary-level economics education remains limited. This study aims to address this gap by proposing a comprehensive CMFS pedagogical framework—encompassing content, mode, faculty, and students—to guide the development of EOS teaching in higher education. Using a qualitative review of international policy documents, institutional practices, and China’s emerging EOS education initiatives, the study analyzes how standards-related knowledge is currently positioned within tertiary economics curricula and identifies barriers to effective implementation. The findings show that EOS has not yet been systematically incorporated into university-level economics programs, largely due to insufficient research, limited course offerings, and inadequate faculty expertise. Global organizations have begun introducing EOS elements into economics education plans, and China has taken early steps to embed standards into tertiary-level teaching and research. The proposed CMFS framework provides practical approaches for strengthening EOS pedagogy, including integrating EOS modules into existing economics courses, diversifying teaching methods, and building faculty capacity. The study concludes that coordinated efforts among governments, educational institutions, industry stakeholders, standards bodies, and international organizations are essential to advance EOS education. Strengthening multidisciplinary and cross-border collaboration will support deeper theoretical development and enhance the long-term contribution of EOS teaching to the evolution of economics education.